Mechanisms of the penetration of ultra-high molecular weight polyethylene composite beams. (July 2016) - Attwood, J.P.; Russell, B.P.; Wadley, H.N.G.; Deshpande, V.S.
Highlights: Two dimensional ballistic impact experiments are reported. Mechanisms of failure immediately under projectile are observed. Indirect tension is inferred as the critical failure mechanism. Abstract: A number of mechanisms have been proposed for the penetration of laminates comprising ultra-high molecular weight polyethylene (UHMWPE) fibres in a polymeric matrix. Two-dimensional ballistic experiments are conducted in order to directly observe the transient deformation and failure processes occurring immediately under the projectile via high-speed photography. Two sets of experiments were conducted on [0°/90°]n laminate beams. First, back-supported and free-standing beams were impacted by cuboidal projectiles of varying mass and fixed geometry. The observations indicate that in both cases, failure occurs in a progressive manner, with plies first failing immediately under the impact zone. The dynamic failure mode is qualitatively similar to that in a quasi-static indentation tests, and attributed to tensile ply failure by the generation of indirect tension within the plies. Direct membrane stretching is ruled out as failure that occurred with negligible beam deflection. In the second set of experiments, the projectile mass was kept constant and its width varied. No dependence of the projectile width was observed in either quasi-static indentation or dynamic penetration tests. This strongly suggests that failure is not governed by a shear process at the edge of the projectile. The observations presented here therefore suggest that tensile ply failure by indirect tension rather than membrane stretching or shear failure at the edges of the projectile is the dominant penetration mechanism in UHMWPE laminates.